Analysis of occupational exposure of healthcare workers in the years 1998–2013 for bloodborne pathogens on the example of the hospital of the surgical profile - Anna Szczypta (Medycyna Pracy, 2014)
Background: To analyze occupational exposures to blood-borne pathogens among workers of a 130-bed hospital of surgical profile in the Małopolska province. Material and Methods: All cases of occupational exposure recorded in the hospital in the years 1998–2013 were analyzed, taking into account exposure rates (no. of incidents / no. of exposed workers ×100%) and the frequency, circumstances, professional groups, hospital staff, the place of rendered services and type of exposure. Results: Average rates of exposure for all workers, regardless of the wards, ranged in different years from 4.3% (2006) to 12.6% (2013), and the average value in the whole period was 7.3% (±2.39). The majority of exposure cases were reported among nurses – 67.8%, followed by physicians – 29.7%, the lowest number of cases was found among other employees – 1.5%. The proportion of injuries in the years 1998–2013 did not show a significant decreasing trend (p = 0.356). Among physicians there was a significant trend of an exponential character (p = 0.002). Among other workers no significant change was observed in the period under consideration. Over the analyzed period the distribution of exposure showed a downward trend for nurses (p = 0.001) and upward trend for physicians (p < 0.001). There was a significant downward trend in the percentage of needle-sticks, and an upward trend in exposures during surgery. Conclusions: The reported trends were linked with the recent introduction of safe equipment and the increased number of surgeons’ reports on exposure incidents. Due to differences between health care units there is a necessity to keep reliable records of exposure by individual units. Med Pr 2014;65(6):723–732